Generation, interrogation, and future applications of microglia-containing brain organoids - Julia Di Stefano; Federica Di Marco; Ilaria Cicalini; Una FitzGerald; Damiana Pieragostino; Marleen Verhoye; Peter Ponsaerts; Elise Van Breedam (Neural Regeneration Research)
Brain organoids encompass a large collection of in vitro stem cell–derived 3D culture systems that aim to recapitulate multiple aspects of in vivo brain development and function. First, this review provides a brief introduction to the current state-of-the-art for neuro-ectoderm brain organoid development, emphasizing their biggest advantages in comparison with classical two-dimensional cell cultures and animal models. However, despite their usefulness for developmental studies, a major limitation for most brain organoid models is the absence of contributing cell types from endodermal and mesodermal origin. As such, current research is highly investing towards the incorporation of a functional vasculature and the microglial immune component. In this review, we will specifically focus on the development of immune-competent brain organoids. By summarizing the different approaches applied to incorporate microglia, it is highlighted that immune-competent brain organoids are not only important for studying neuronal network formation, but also offer a clear future as a new tool to study inflammatory responses in vitro in 3D in a brain-like environment. Therefore, our main focus here is to provide a comprehensive overview of assays to measure microglial phenotype and function within brain organoids, with an outlook on how these findings could better understand neuronal network development or restoration, as well as the influence of physical stress on microglia-containing brain organoids. Finally, we would like to stress that even though the development of immune-competent brain organoids has largely evolved over the past decade, their full potential as a pre-clinical tool to study novel therapeutic approaches to halt or reduce inflammation-mediated neurodegeneration still needs to be explored and validated.